2019
DOI: 10.33073/pjm-2019-048
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance Among Uropathogenic Escherichia coli

Abstract: Urinary tract infections (UTIs) belong to the most common community-acquired and nosocomial infections. A main etiological factor of UTIs is uropathogenic Escherichia coli (UPEC). This review describes the current state of knowledge on the resistance of UPEC to antibiotics recommended for the treatment of UTIs based on the available literature data. Nitrofurantoin and fosfomycin are recommended as first-line therapy in the treatment of uncomplicated cystitis, and the resistance to these antimicrobial agents re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
161
2
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 206 publications
(182 citation statements)
references
References 94 publications
6
161
2
13
Order By: Relevance
“…Currently, the empirical treatment of UTIs is an issue of concern due to the increasing rates of antibiotic resistance. The resistance to trimethoprim-sulfamethoxazole (TMP-SMZ), ciprofloxacin, and amoxicillin-clavulanate (AMC) among UPEC isolates is higher in developing countries (ranging from ~50% to 85%) than in developed countries (ranging from 3% to 40%) (Kot, 2019). Routine standard antimicrobial susceptibility testing must be performed in order to reduce the rates of inappropriate empirical antibiotic therapy of UTIs and thereby decrease the occurrence of multidrug-resistant (MDR) UPEC (Adamus-Białek et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the empirical treatment of UTIs is an issue of concern due to the increasing rates of antibiotic resistance. The resistance to trimethoprim-sulfamethoxazole (TMP-SMZ), ciprofloxacin, and amoxicillin-clavulanate (AMC) among UPEC isolates is higher in developing countries (ranging from ~50% to 85%) than in developed countries (ranging from 3% to 40%) (Kot, 2019). Routine standard antimicrobial susceptibility testing must be performed in order to reduce the rates of inappropriate empirical antibiotic therapy of UTIs and thereby decrease the occurrence of multidrug-resistant (MDR) UPEC (Adamus-Białek et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that 40% of women and 12% of men experience UTI infection at least once in their lifetime. 1 Both genders are affected by UTIs, but the infections are much more common in women aged 15-44 years. 2 This kind of infection is responsible for 40% of nosocomial infections and 50% of bacterial infections which prolongs hospitalization and increases mortality.…”
mentioning
confidence: 99%
“…3 In addition, healthcare-associated UTI, as one of the most common infections that occur in healthcare centers, is considered a significant threat to patients due to increased mortality. 1 Community-acquired UTI is also one of the most prevalent community infections. Uropathogenic Escherichia coli (UPEC) is the primary cause of UTIs in both healthcare centers and community.…”
mentioning
confidence: 99%
See 2 more Smart Citations